KAJIAN PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SANITASI BERBASIS MASYARAKAT (PSBM) DI KELURAHAN MANGUNHARJO, SEMARANG - Ivan Kurnia Adi; Mardwi Rahdriawan (Jurnal Pengembangan Kota, 2016)
The tendency of the existing infrastructure is not in accordance with the needs of the community because it is top down. Therefore, this study aims to assess community participation in managing community-based sanitation. Studies conducted focusing on participatory processes and the level of community participation in the provision of sanitation in the village program Mangunharjo precisely in RT 03 and 04 RW I. The method used in this research is quantitative and qualitative. The level of community participation in the management of the sanitation program has high participation category that has meaning on the degree of power-sharing community which has occurred rights, responsibilities and authority between the community and government to participate. Meanwhile, at the stage of organizing the participation category includes medium category (tokensm) in which the wishes of the people has been discussed, but the decision rests with the government. It is influenced by the role of the Village and Chairman of RT / RW is too dominant so that the public is not very enthusiastic in participating at the stage of organizing and resigned to the decision of the facilitator. Implementation of the program when viewed from the principle pelaksaaan almost matches that is about 80%, planning, implementation, and evaluation is fully in accordance with the principle only at the stage of organizing has obstacles described earlier which resulted in incompatibility in principle with the implementation of the program. That there is a relationship between the facilitator and community involvement, if the facilitator can perform their duties well as explaining the program well and excessive interference, then the public will enthusiastically participate. The Government needs to show its commitment in the implementation of the provision of community-based sanitation program (PSBM) in terms of giving people an opportunity to participate fully in sanitation management stages.